Efficacy and Safety of Moxidectin, Synriam, Synriam-Praziquantel versus Praziquantel against Schistosoma haematobium and S. mansoni Infections: A Randomized, Exploratory Phase 2 Trial. - Beatrice Barda; Jean T Coulibaly; Maxim Puchkov; Jörg Huwyler; Jan Hattendorf; Jennifer Keiser (Public Library of Science (PLoS), 2016)
BACKGROUND:Schistosomiasis affects millions of people, yet treatment options are limited. The antimalarial Synriam (piperaquine 150 mg/arterolane 750 mg) and the anthelminthic moxidectin revealed promising antischistosomal properties in preclinical or clinical studies. METHODOLOGY:We conducted two single-blind, randomized exploratory Phase 2 trials in Schistosoma mansoni and S. haematobium-infected adolescents in northern and central Côte d'Ivoire. Our primary endpoints were cure rates (CRs) and egg reduction rates (ERRs) based on geometric mean and safety. Each subject was asked to provide two stool samples (S. mansoni trial) for Kato-Katz analysis or three urine samples (S. haematobium trial) for urine filtration and one finger prick for malaria screening at baseline and follow-up. Participants were randomly assigned to either moxidectin, Synriam, Synriam plus praziquantel or praziquantel. PRINCIPAL FINDINGS:128 adolescents (age: 12-17 years) were included in each study. Against S. haematobium moxidectin and Synriam revealed low efficacy. On the other hand, Synriam plus praziquantel and praziquantel yielded CRs of 60.0% and 38.5% and ERRs of 96.0% and 93.5%, respectively. CRs observed in the treatment of S. mansoni were 13.0%, 6.7%, 27.0%, and 27.6% for moxidectin, Synriam, Synriam plus praziquantel and praziquantel, respectively. ERRs ranged from 64.9% (Synriam) to 87.5% (praziquantel). CONCLUSION/SIGNIFICANCE:Synriam and moxidectin show low efficacy against S. haematobium, hence an ancillary benefit is not expected when these drugs are used for treating onchocerciasis and malaria in co-endemic settings. Further studies are needed to corroborate our findings that moxidectin and Synriam show moderate ERRs against S. mansoni.